Correction: Strain mapping inside an individual processed vertical nanowire transistor using scanning X-ray nanodiffraction. Issue 13 (23rd March 2022) - Dzhigaev, Dmitry; Svensson, Johannes; Krishnaraja, Abinaya; Zhu, Zhongyunshen; Ren, Zhe; Liu, Yi; Kalbfleisch, Sebastian; Björling, Alexander; Lenrick, Filip; Balogh, Zoltan Imre; Hammarberg, Susanna; Wallentin, Jesper; et al.
Abstract : Correction for 'Strain mapping inside an individual processed vertical nanowire transistor using scanning X-ray nanodiffraction' by Dmitry Dzhigaev et al., Nanoscale, 2020, 12, 14487–14493, DOI: ; 10.1039/D0NR02260H .